An experimental approach to the estimation of stiffness changes in RC elements exposed to bending and high temperature. (15th August 2020) - Głowacki, Michał; Kowalski, Robert
Highlights: Experimental study on full-size RC beams exposed to simultaneous action of load and high temperature. Tension or compression zone of cross-section heated to fire temperature. The estimation of stiffness changes based on deflection measurements. The cross-section stiffness of the beam with the heated tension zone decreases rapidly at the initial heating stage. During heating the cross-section stiffness of the beam with the heated compression zone remains constant for a long time. Abstract: This paper presents the results of tests for possible stiffness changes in bent reinforced concrete elements exposed to simultaneous action of load and high temperature. The above issue plays a critical role in the advanced analysis of complex RC structures subjected to fire. In order to examine this issue, an experimental study of 24 full-size RC beams was performed. All beams were divided into 8 series according to 3 factors: (1) the cross-section zone exposed to high temperature – tension or compression zone, (2) reinforcement ratio – 0.44 or 1.13%, (3) load level in reference to ultimate load capacity at room temperature – 50 or 70%. The pure bending part of the beam was heated. Stiffness changes estimated on the basis of deflection measurement. The cross-section stiffness of the beam with the heated tension zone decreases rapidly at the initial heating stage. A decrease of 60–80% in cross-section stiffness is observed at reinforcement temperature of 200–300 °C. When reinforcement temperature is about 500 °C, the cross-section stiffness may be only 10–15% of its value at room temperature. It has also been found that the model recommended in Eurocode 1992-1-2 characterizing mechanical properties of tensile steel in high temperature may be used for the adequate prediction of stiffness decrease in the cross-section with the heated tension zone. It can be assumed that during heating the stiffness of cross-sections with the heated compression zone will remain approximately constant for some time. It will only start to decrease when the strain of concrete exposed simultaneously to load and high temperature begins to exceed its free thermal strain. This paper presents a simplified method to estimate the cross-section stiffness in bent reinforced concrete elements with the heated tension or compression zone.